ANALYSIS OF DOCUMENTATION OPPORTUNITIES OF CULTURAL HERITAGE SAMPLES WITH TERRESTRIAL PHOTOGRAMETRY METHODS - Bilici, Ebru; Uçar, Zennure; Akay, Abdullah Emin; Genç, Musa (Kahramanmaras Sutcu Imam University, 2021)
Nowadays, as in many sectors, natural and cultural resources face the danger of extinction due to misuse and consumption-oriented life in tourism. Within the framework of the sustainability tourism principle, these resources should be determined, protected, and developed. With the advance technology, the use of photogrammetry offers new methods for surveying natural and cultural resources. In this study, the photographs of two historical sites were taken with a high-resolution handheld camera in order to evaluate the potential of terrestrial photogrammetry approach in the cultural heritage. Then, these photographs were used to develop three-dimensional models of the two sites using two different software-Agisoft Metashape and 3D Zephyr Free. For this study, two important cultural and historical heritages were selected; both located in the center of Giresun province in Turkey. The 3D models of the heritages developed using two software were compared to evaluate the capability of the software. In the evaluation process, 13 photographs for the historical door and 50 photographs for the shrine were used to generate 3D models. According to the evaluation of the models, it was observed that the model generated for the front surface of the Public Garden door provided more detailed and accurate results in both software. When these two programs are compared for the shrine, Agisoft Metashape produced a better 3D model than 3D Zephyr. The results also showed that the photographs obtained from a low-cost handheld camera could provide highly accurate and precise data for documentation of historical and cultural heritages.

Günümüzde birçok sektörde olduğu gibi doğal ve kültürel kaynaklar yanlış kullanım ve turizmde tüketim odaklı yaşayış nedeniyle yok olma tehlikesi ile karşı karşıya kalmaktadır. Tuzim de sürdürülebilirlik ilkesi çerçevesinde bu kaynakların tespit edilmesi korunması ve geliştirilmesi gerekmektedir. İlerleyen teknoloji ile birlikte tespit aşamasında fotogrametrik yöntemlerde kullanım imkanları ortaya çıkmıştır. Çalışmada yersel fotogrametrik yöntemlerin miras niteliği taşıyan kaynakların kayıt altına alınmasında potansiyelini değerlendirmek amacıyla iki örnek tarihi yapının yüksek çözünürlüklü kamera ile fotoğrafları çekilmiştir. Daha sonra, Agisoft ve 3D Zephyr Free programı yardımıyla foroğraflar işlenerek üç boyutlu modelleri oluşturulmuştur. Çalışmada, Giresun ili merkezde bulunan önemli kültürel miras örneklerinden Giresun Millet Bahçesi girişindeki tarihi kapı ve Seyyit Vakkas Türbesi incelenmiştir. Modelleme sırasında kapı için 13 ve türbe için 50 olmak üzere farklı fotoğraf sayıları kullanılmıştır. Programlarla model oluşturma sırasında kullanılan noktalar ve ara yüzler incelenmiştir. Modellere ilişkin değerlendirmelere göre Millet Bahçesi kapısının ön yüzeyi için oluşturulan modelde her iki programında detaylı sonuç verdiği gözlemlenmiştir. Bu iki program türbe için kıyaslandığında ise Agisoft Metashape 3D Zephyr’e göre daha iyi bir model ortaya çıkarmıştır. Sonuçlar kültürel miras niteliği taşıyan tarihi yapıların kayıt altına alınmasında yersel photogrametrik yöntemlerin yüksek doğrulukta ve hassasiyette veriler sağlayabileceğini göstermiştir.
KÜLTÜREL MİRAS ÖRNEKLERİNİN YERSEL FOTOGRAMETRİ YÖNTEMLERLE KAYIT ALTINA ALINMA IMKANLARININ ANALİZİ
Keywords: Photogrammetry and Remote Sensing; Fotogrametri ve Uzaktan Algılama